Footbomb from Cassia alata Linn. Roots Extract - Samuel, Lihan; Sabella, Justin; Aldrin Felix, Simbas; Thracesy Munah, Assan; Showkat, Ahmad Bhawani (2025)
This study innovates "Footbomb"—a natural antimicrobial foot cleanser formulated from Cassia alata (Sena alata) Linn. root extract—as an ecofriendly alternative to conventional foot care products. S. alata Linn. roots, known for their medicinal properties, were extracted using 70% ethanol to isolate bioactive compounds, which also additionally incorporate silver nanoparticles that were biosynthesized using S. alata Linn. root aqueous extract in the formulations. These products will be produced into solid and liquid Footbomb formulations. These biosynthesized nanosilver particles demonstrated broad-spectrum antimicrobial activity against Grampositive bacteria (e.g., Staphylococcus aureus, Bacillus cereus), Gramnegative bacteria (e.g., Escherichia coli, Pseudomonas aeruginosa), and fungi (e.g., Candida albicans). Preliminary human trials indicated a >70% reduction in microbial load, supporting its potential as a natural remedy for foot infections. The findings highlight the viability of Sena alata Linn. root extract—enhanced with biosynthesized silver nanoparticles—in commercial foot care products, offering a sustainable, plant-based solution. Further clinical trials are recommended to validate long-term safety and effectiveness, paving the way for an innovative, eco-conscious healthcare product.